Prognostic, predictive and potential surrogate markers in castration-resistant prostate cancer. Issue 6 (June 2015) - Aziz, Atiqullah; Kempkensteffen, Carsten; May, Matthias; Lebentrau, Steffen; Burger, Maximilian; Chun, Felix K-H; Brookman-May, Sabine
<x xml:space="preserve">Abstract</x> Several novel therapeutic agents have demonstrated improvement of overall survival and further patient relevant endpoints in the setting of castration-resistant prostate cancer. Nevertheless, two questions have become increasingly relevant: are there any prognostic or predictive markers that could ease clinical decision-making using risk stratification and risk-adapted treatment in order to provide a benefit for the patient? Furthermore, against the background of increasing possibilities of therapy sequencing in clinical practice and in the clinical trial landscape in castration-resistant prostate cancer, does an isolated evaluation of overall survival reliably mirror the benefit attributable to a single compound? To address both these questions, suitable parameters serving as surrogates for intermediate and long-term endpoints and reflecting individual benefit, respectively, need to be identified and proven.